Stable perovskite solar cells using tin acetylacetonate based electron transporting layers. Issue 6 (9th May 2019) - Abuhelaiqa, Mousa; Paek, Sanghyun; Lee, Yonghui; Cho, Kyung Taek; Heo, Sung; Oveisi, Emad; Huckaba, Aron Joel; Kanda, Hiroyuki; Kim, Hobeom; Zhang, Yi; Humphry-Baker, Robin; Kinge, Sachin; et al.
Abstract : High performing planar-type perovskite solar cells and mini-modules are fabricated by incorporating passivated tin oxide based on non-colloidal acetylacetonate precursors. Abstract : Organic–inorganic lead halide perovskites with over 23% power conversion efficiency have attracted enormous academic and industrial attention due to their low-cost fabrication and high device performance. Self-passivated tin oxide as an electron transport layer has shown potential mainly due to the enhanced electron transfer, stability and reduced hysteresis device features. Here we report on novel, non-colloidal tin oxide precursors based on acetylacetonate (one halide free and two halogenated with Cl and Br respectively). We explore the unique film morphology acquired from the non-colloidal precursors and the improved device performance they yield. Our results show that the halide residue in the films plays an impactful role in the thermal durability of the fabricated SnO2 film, as well as providing a passivation layer. Moreover, our optimized tin oxide films achieved an unprecedented power conversion efficiency of 22.19% in planar perovskite solar cells (21.4% certified by Newport), and once upscaled to large-area modules, 16.7% devices based on a 15 cm 2 area were achieved.